AN APPLICATION OF COMIC STRIP IN INCREASING SPEAKING SKILL TO THE TENTH GRADE OF SMA N 22 OF PALEMBANG - Noviati, Noviati (Jurnal Dosen Universitas PGRI Palembang)
AbstractÂ Â Â Â Â Â Â Â Â Â Â Â The objective of this study was to know whether or not the application of comic strip could increase speaking skill for the tenth graders of SMA N 22 Palembang. In this study, the writer used weak experimental method. The population of thisÂ study consisted of 153 students of SMA N 22 Palembang. The writer chose one class as the sample of the study. The sample was selected by using convenience sampling method. There were 34 students as the samples of this study. The data were collected by using written test.Â Â Â Â Â Â Â Â Â Â Â The result showed, in the pretest, the highest score was 8, while the lowest was 5 with the mean scores was 7.35. However, in the posttest, the highest score was 12, while the lowest score was 6 with the mean scores 8.35. It could be interpreted that comic strip was mostly effective to be used in increasing speaking skill for the tenth graders of SMA N 22Palembang. Thus, the research hypothesis stated â It is effective teaching writing a descriptive paragraph by using mind mappingâ was accepted and the null hypothesis was rejected.Â Keywords: Application, Comic Strip, Speaking Skill